A unified macro-modelling approach for masonry-infilled RC frames strengthened with composite materials. (15th November 2020) - Pohoryles, D.A.; Bournas, D.A.
Highlights: A simplified macro-model for composite strengthened infills is proposed. The model includes an increase in compressive strut width and an additional tensile tie. The model is calibrated based on a database of available experimental data. The empirical equations were shown to achieve high correlation with experiments. Abstract: Non-structural masonry infills in existing reinforced concrete (RC) frame structures are known to affect their seismic behaviour significantly with potential detrimental effects. Increasing experimental evidence is available for the use of composite materials, such as fibre-reinforced polymers (FRP) and textile reinforced mortars (TRM), for in-plane retrofitting of brittle masonry infills. In order to apply such strengthening solutions in practice, adequate analytical models for predicting the behaviour are needed, however the large variation in infill properties already makes modelling the behaviour of non-retrofitted infills a challenge. Based on existing experimental and numerical studies on retrofitted infills, a macro-model is proposed, comprising a tie to account for the tensile strength of the composites materials, but also an increased compressive strut width due to the composite materials improving connection of the infill to the frame. After compiling a database of experimental data for composite retrofitted specimens tested in the literature, empirical equations for tie and strut strength was obtained. These equations constitute the first unified approach for FRP- and TRM-strengthened infills and were verified against the largest database of experimental results to date. The strut model was calibrated for the increase in strut width in terms of experimentally obtained stiffness increase, while the tie model was determined based on the remaining increase in strength. The empirical equations were shown to achieve a relatively high correlation with experimental results and to represent the mechanics of tested specimens well in terms of observed damage, hence indicating their potential for use as design-oriented equations for composite strengthened infills.